2021
DOI: 10.35631/ijepc.643003
|View full text |Cite
|
Sign up to set email alerts
|

Investigating English Writing Problems Among High Achiever Post-Upsr Learners in Sabah

Abstract: The purpose of the study was to investigate the writing problems faced by the Post-UPSR learners during their primary school years. The data was obtained from 217 high achiever learners who scored an A on the UPSR. These learners, who had completed primary schools and taken the UPSR exam, are now enrolled in secondary schools as Form 1 learners. The method used is a quantitative study. A questionnaire was used as the instrument in the study. The analysis of the study uses SPSS which involves frequency and perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Moreover, numerous studies indicated that inadequate vocabulary is a significant obstacle that prevents students from producing high-quality writing among ESL primary school students (e.g. Daud et al, 2021;Ghulamuddin et al, 2021;Kumaran & Krish, 2021). While the importance of vocabulary in writing is well-established, many teachers agreed that students face significant challenges when it comes to developing their vocabulary skills.…”
Section: Lack Of Vocabularymentioning
confidence: 99%
“…Moreover, numerous studies indicated that inadequate vocabulary is a significant obstacle that prevents students from producing high-quality writing among ESL primary school students (e.g. Daud et al, 2021;Ghulamuddin et al, 2021;Kumaran & Krish, 2021). While the importance of vocabulary in writing is well-established, many teachers agreed that students face significant challenges when it comes to developing their vocabulary skills.…”
Section: Lack Of Vocabularymentioning
confidence: 99%
“…Additionally, 30% of them had difficulty in constructing writing with correct sentence structure. Furthermore, within the Malaysian context, Daud et al (2021) conducted a study with high school students in their first year. The results revealed that students encountered writing difficulties in vocabulary, which it ranked the highest score (56.7%), along with grammar difficulties (26.3%).…”
Section: Students' Present Situation Analysismentioning
confidence: 99%